Teachers' assessment competence: Integrating knowledge-, process-, and product-oriented approaches into a competence-oriented conceptual model. (November 2018) - Herppich, Stephanie; Praetorius, Anna-Katharina; Förster, Natalie; Glogger-Frey, Inga; Karst, Karina; Leutner, Detlev; Behrmann, Lars; Böhmer, Matthias; Ufer, Stefan; Klug, Julia; Hetmanek, Andreas; Ohle, Annika; et al.
Abstract: In this article, we present a new model of teachers' assessment competence. The model is based on the educational competence concept, thus defining competences to be context-specific, learnable cognitive dispositions that are needed to successfully cope with specific situations. Integrating research on assessment processes, practices, and products, we specify the range of situations our model applies to, and discuss how its elements may become involved and measurable in a variable assessment process. The model aims to inspire future integrative research on the description, explanation, prediction, and promotion of teachers' assessments in various situations. Graphical abstract: Highlights: A new conceptual model on teachers' assessment competence is introduced. Competence, as its base, is a learnable situation-specific cognitive disposition. The model integrates research on assessment processes, practices, and products. We discuss how its elements become measurable in a variable assessment process. The model aims to inspire integrative research on assessment.